The Feasibility and Efficacy of Ultrasound-Guided C2 Nerve Root Coblation for Cervicogenic Headache - Wu, Baishan; Yue, Li; Sun, Fenglong; Gao, Shan; Liang, Bing; Tao, Tao (Pain medicine (Malden, Mass.), 2019)
Abstract Objective The cervicogenic headache is a syndrome caused by dysfunction of the upper cervical spine and its component bony, disc, and/or soft tissue elements. The C2 nerve root may play a pivotal role in cervicogenic headache. In this retrospective study, we evaluated the feasibility and efficacy of ultrasound-guided C2 nerve root coblation in managing 26 patients with cervicogenic headache. Design and Setting The data were collected retrospectively by reviewing the patient’s medical records and pain questionnaires. Subjects and Methods A total of 109 patients with cervicogenic headache sustained for at least six months were identified. Of those patients, 26 had a visual analog scale score ≥6 and subsequently underwent an ultrasound-guided C2 nerve root coblation. Results All 26 patients had >50% pain relief one day after coblation. Twenty-three of the 26 patients (92.31%) had a decrease in their pain score of 50% or more at 24-week follow-up. The mean pain score was 7.38 ± 1.13 before coblation and 1.85 ± 0.83 one day after coblation (Bonferroni-adjusted P < 0.001). At 12 and 24 weeks after coblation, the mean pain scores were 2.96 ± 0.96 (P < 0.001) and 3.08 ± 1.38 (P < 0.008), respectively. Conclusions C2 nerve coblation may provide the majority of patients with a pain relief period as long as 24 weeks. And ultrasound guidance is an efficient method with which to perform coblation.